Antibiotics susceptibility of quinolones against Salmonella spp. strains isolated and molecularly sequenced for gyrA gene. (January 2018) - Macías-Farrera, Guadalupe Patricia; de Oca Jiménez, Roberto Montes; Varela-Guerrero, Jorge; Tenorio-Borroto, Esvieta; Rivera-Ramírez, Fabiola; Monroy-Salazar, Humberto Gustavo; Yong-Angel, Gilberto
Abstract: Drug-resistant Salmonella is frequently detected in most parts of the world, and its rate of resistance has increased significantly in recent years. However, this study aimed to evaluate the minimum inhibitory concentration (MIC, determined with the Kirby-Bauer method) of quinolones in 86 Salmonella spp. strains isolated from pigs. Both the inside and outside of the QRDR region of strains were sequenced. The DNA sequence of the QRDR region of Salmonella spp. revealed the mutations S83F, D87N and S83Y. The region outside the QRDR showed a mutation in L582G. Forty-five isolates of Salmonella ssp. were categorized as quinolone-resistant; out of these, 16 corresponded to Salmonella enterica and isolates showed intermediate resistance (6.25%) to nalidixic acid. Three isolats (18.6%) were resistant to ampicillin; two (12.5%) were resistant to carbenicillin. Moreover, three (18.7%) isolates were resistant to gentamicin, nitrofurantoin and pefloxacin, and 8 (50%) were resistant to trimethoprim/sulfamethoxazole. Six percent of Salmonella spp. strains showed less resistance to antimicrobial agents compared to S. Thyphimurium (18%). The resistance to individual quinolones varied by serotypes. For S. anatum and S. Reading, it was 12.25%, and for S. choreaeaesuis, S. typhimurium monofasica, 6.25%. In contrast, S. agona, S. bredeney and S. london were sensitive to these antibiotics. In conclusion, quinolones have become the drugs of choice for the treatment of severe Salmonella infections. The study of mutations outside the QRDR region opens up new insights about the resistance of Salmonella to fluoroquinolones. Highlights: Quinolones MIC in 86 Salmonella spp. strains from pigs were evaluated. Sequence DNA of Salmonella spp. revealed the mutations S83F, D87N and S83Y. The region outside the QRDR showed a mutation in L582G. Quinolones consider as drugs of choice for the treatment of Salmonella infections. Mutations outside QRDR are new for resistance of Salmonella to fluoroquinolones.